Electrochemical Sensor for Cu(II) Based on Carbon Nanotubes Functionalized with a Rationally Designed Schiff Base - Tamborelli, Luis Alejandro (2025)
This work proposes a new strategy for the electrochemical quantification of Cu(II) using glassy carbon electrodes (GCEs) modified with a nanohybrid of multiwall carbon nanotubes (MWCNTs) non-covalently functionalized with a rationally designed Schiff base containing different groups (SB-dBA). The principle of sensing was the complexation of Cu(II) by the Schiff base that supports the MWCNTs at the open-circuit potential, followed by a reduction step at −0.600 V and further linear sweep anodic stripping voltammetry (LSASV) in a 0.200 M acetate buffer solution of pH 5.00. The linear range goes from 10 to 200 μg L−1, with a sensitivity of (0.79 ± 0.07) µA L µg−1 (R2 = 0.991), a detection limit of 3.3 μg L−1, and a reproducibility of 8.0% for the same nanohybrid (nine electrodes) and 9.0% for four different nanohybrids. The proposed sensor was very selective for Cu(II) even in the presence of Pb(II), Fe(II), As(III), Cr(III), Cd(II), and Hg(II), and it was successfully used for the quantification of Cu(II) in different water samples (tap, groundwater, and river) without any pretreatment.